PEMBERIAN ASI EKSKLUSIF DAN BERAT BADAN LAHIR RENDAH PADA BALITA STUNTING DI WILAYAH DESA TANAK BEAK NUSA TENGGARA BARAT - DEWI, NOVIANTI TYSMALA; LASTYANA, WIWIN (GANEC SWARA, 2023)
Stunting is an indicator of health in toddlers, namely chronic nutritional status which results in stunted growth and development. Low birth weight and lack of exclusive breastfeeding are factors that can cause stunting in toddlers. The aim of this research is to analyze differences in exclusive breastfeeding and birth weight among stunted toddlers in the Tanak Beak Village area, West Nusa Tenggara. The research design was cross sectional with a research sample of 60 stunted toddlers aged 6-59 months who were collected using a purposive sampling method. Nutritional status data was collected by measuring using a baby length board and stadiometer with the criteria of a Z-score TB/U or PB/U of less than -2 SD. Data on characteristics and exclusive breastfeeding were obtained through interviews and birth weight was obtained from secondary data from the Community Health Center. Data were analyzed using T-test. The results of the study showed that there was no significant difference in low birth weight (p=0.882) in stunted toddlers, while there was a difference in exclusive breastfeeding (p=0.041) in stunted toddlers in the posyandu1 and posyandu2 areas. The conclusion is that there is no difference in low birth weight in stunted toddlers, while there is a difference in exclusive breastfeeding in stunted toddlers in the posyandu1 and posyandu2 areas. There is a need to increase coverage and efforts to improve the quality of exclusive breastfeeding to optimize efforts to prevent stunting.